Pemberdayaan Siswa melalui Strategi Promosi Inovatif untuk Produk Kuliner Halal (Pempek) di SMA Islam Al-Amalul Khair Palembang - Christian Yosua Salomo Aritonang; Rismarini Rismarini; Waliah Nur Rahayu; Rani Revina Putri (Pusat Riset dan Inovasi Nasional, 2026)
This international collaborative community service program is designed to transform the entrepreneurial paradigm of students at Al-Amalul Khoir Islamic High School in Palembang by strengthening innovative promotional strategies for local culinary products, particularly pempek. This initiative was motivated by the low competitiveness of partner products due to the use of conventional packaging, minimal application of packaging technology, and the lack of a strong and marketable brand identity. These conditions impact the limited market reach and economic value of the students' products. The program's implementation method uses a Participatory Rural Appraisal (PRA) approach, which emphasizes active participation by partners in every stage of the activity. Program stages include the delivery of theoretical material on entrepreneurship and halal product marketing, a creative packaging design workshop focused on branding, and hands-on practice in the application of hygienic and food-standard vacuum packaging technology. This approach allows for contextual and applicable learning for participants. The results of the activity showed a significant increase in students' understanding of the legal and regulatory aspects of halal labeling, increasing from 34.5% to 89.7%. Furthermore, students' technical skills in designing innovative and distinctive packaging also significantly improved. The program concluded that integrating modern packaging technology with appropriate branding strategies can increase the competitiveness and economic value of local products in a sustainable manner.